FACTORS AFFECTING SICK BUILDING SYNDROME (SBS) COMPLAINTS AMONG WORKERS: LITERATURE REVIEW - Saputro, Anjas Andi (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Sick Building Syndrome (SBS) is a set of health symptoms that occur due to someone’s activity in a room or building. Recently, humans tend to do the work and activities inside a building. Therefore, this increases the risk of symptoms such as dizziness, headaches, nasal, skin and throat irritations. The aim of this study was to determine the factors that affected SBS symptoms on workers using a literature review method. All articles were searched and retrieved from electronic databases such as Pubmed, Google Scholar and Emerald Insight by looking at various significant factors of SBS in articles published from 2010 to 2020. A total of 31 journal articles reporting significant factors of SBS were collected. These factors include personal factors (age, gender, history of illness/allergies, smoking habits); physical factors (temperature, light, humidity, ventilation, noise); chemical factors (CO2, CO, VOCs, Formaldehyde); psychosocial factors (weak psychosocial, working period, working time, job satisfaction); and work environment factors (cigarette smoke, room hygiene and cleanliness, building design, unpleasant odor, IAQ). It is suggested that workers need to maintain personal health status, practice relaxation, wear a mask and not to smoke. Moreover, companies should conduct a regular health check and monitor the work environment.